Peculiarities of Ukraine's foreign trade for the period 2018-2020 in contexts of global and regional value chains - R.V. Sevastyanov (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
The article investigates international trade activity of Ukraine for the period 2018-2020. Ukrainian companies tend to be providing integration into global value chains. The research confirms positive dynamics in foreign trade of Ukraine for the period 2018-2020. The Ukrainian enterprises mainly exports low value-added goods and imports high value-added goods. Development of Ukraine's economy requires successful integration into global production and distribution networks with a reduction in the processing of raw materials with insignificant added value. The research confirms positive dynamics in foreign trade of Ukraine for the period 2018-2020. The research methods used in the study are as follows: analysis and study of literature, scientific description, Internet research, statistical and structural survey, data sheet presentation. The research proved that the economic relations between Ukraine and trade partners demonstrate significant increase of the foreign trade within the global value chains (GVC). Ukrainian companies tend to be providing integration into global value chains. Agricultural and industrial products exported from Ukraine accounted for 42.1% of the total international sales in 2020. Recommendations for Ukraine's integration into global and regional business services can include developing services in context of GVC, developing international cooperation between enterprises on global business platforms. The basis for successful integration into GVC must be the development of innovative ecosystems of industrial high technologies. It is important to develop innovative industrial high-tech ecosystems for successful integration into GVC. Ukrainian exports are dominated by metallurgical and agricultural products. Its feature is the high proportion of intermediate goods used as a source material for the production of other final consumer goods. The author tries to formulate modern directions of development for further integration of the Ukrainian economy into global and regional value chains. Recommendations for Ukraine's integration into global and regional business services can include developing services, developing international cooperation between enterprises on global business platforms.